2015
DOI: 10.1155/2015/197241
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA181a Is Overexpressed in T-Cell Leukemia/Lymphoma and Related to Chemoresistance

Abstract: MicroRNAs (miRs) play an important role in tumorogenesis and chemoresistance in lymphoid malignancies. Comparing with reactive hyperplasia, miR181a was overexpressed in 130 patients with T-cell leukemia/lymphoma, including acute T-cell lymphoblastic leukemia (n = 32), T-cell lymphoblastic lymphoma (n = 16), peripheral T-cell lymphoma, not otherwise specified (n = 45), anaplastic large cell lymphoma (n = 15), and angioimmunoblastic T-cell lymphoma (n = 22). Irrespective to histological subtypes, miR181a overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
(35 reference statements)
2
21
1
Order By: Relevance
“…Acquired drug resistance is an significant obstacle that impairs the success of cancer treatment. Isogenic Dox-resistant sublines were developed as previously reported 14,18 Figure 4C), but also increased apoptosis of the Dox-resistant cells ( Figure 4D).…”
Section: Dox-ncs Inhibited P-gp Induction and Induced Dox-resistant Csupporting
confidence: 63%
See 1 more Smart Citation
“…Acquired drug resistance is an significant obstacle that impairs the success of cancer treatment. Isogenic Dox-resistant sublines were developed as previously reported 14,18 Figure 4C), but also increased apoptosis of the Dox-resistant cells ( Figure 4D).…”
Section: Dox-ncs Inhibited P-gp Induction and Induced Dox-resistant Csupporting
confidence: 63%
“…Accumulating evidence has shown that Dox-treatment could induce tumor cell P-gp expression, resulting in increased drug excretion and multidrug resistance. 18,19 Compared with Dox, Dox-NCs inhibited P-gp expression ( Figure 4A). As the mechanism of action, cytoplasmic ATP concentration was significantly lower, after 48 hours incubation, in Dox-NCs-treated cells (Jurkat 0.63±0.11 nmol/10 6 cells, Namalwa 0.71±0.29 nmol/10 6 cells), when compared with Dox-treated cells (Jurkat 1.34±0.11 nmol/10 6 cells, Namalwa 1.66±0.22 nmol/10 6 cells, P,0.05, Figure 4B).…”
Section: Dox-ncs Inhibited P-gp Induction and Induced Dox-resistant Cmentioning
confidence: 99%
“…As mentioned above, miR-19, which belongs to the miR-17-92 cluster, controlled multiple regulators ( PP2A , PRKAA1 , BIM , and PTEN ) of PI3K signaling which resulted in increased phosphorylation of AKT and the ribosomal S6 protein, which subsequently promoted survival of T-ALL cells [ 44 ]. Additionally, miR-181a could induce chemoresistance in Jurkat T-ALL cells through activating AKT, which will be discussed in detail later [ 59 ]. Moreover, luciferase assay experiments showed that miR-19 directly repressed the expression of CYLD , which plays a predominant role in the negative regulation of NF-κB, inducing activation of the NF-κB downstream program [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…3A and B, the expression of p65 was decreased significantly in celecoxib-treated Jurkat and Hut-78 cells. It is well-known that the NF-κB P65 subunit participates in activating various downstream genes associated with the regulation of apoptosis and induction of MDR (6)(7)(8). Several studies have revealed that Bcl-2 may suppress the activity of multiple pro-apoptotic proteins by binding with P65 (3,6).…”
Section: Celecoxib Inhibits the Expression Of The Mdr-associated Protmentioning
confidence: 99%
“…It is well-known that the NF-κB P65 subunit participates in activating various downstream genes associated with the regulation of apoptosis and induction of MDR (6)(7)(8). Several studies have revealed that Bcl-2 may suppress the activity of multiple pro-apoptotic proteins by binding with P65 (3,6). Additionally, previous studies also confirmed that the majority of the MDR-associated proteins, including P-gp and MRP1, are positively regulated by the NF-κB pathway, and that blockade of the NF-κB pathway may suppress their expression (6,7).…”
Section: Celecoxib Inhibits the Expression Of The Mdr-associated Protmentioning
confidence: 99%